2016
DOI: 10.1007/s13555-016-0134-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acne Keloidalis Nuchae: A Systematic Review of the Literature

Abstract: Acne keloidalis nuchae (AKN) is a chronic inflammatory condition that leads to fibrotic plaques, papules and alopecia on the occiput and/or nape of the neck. Traditional medical management focuses on prevention, utilization of oral and topical antibiotics, and intralesional steroids in order to decrease inflammation and secondary infections. Unfortunately, therapy may require months of treatment to achieve incomplete results and recurrences are common. Surgical approach to treatment of lesions is invasive, may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 31 publications
0
45
0
5
Order By: Relevance
“…The 1064 nm Nd: YAG destroys the hair follicles within the lesions which has some bearing on the inflammation 38. It can be used in conjunction with topical steroids or retinoids and has been found useful in refractory cases.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The 1064 nm Nd: YAG destroys the hair follicles within the lesions which has some bearing on the inflammation 38. It can be used in conjunction with topical steroids or retinoids and has been found useful in refractory cases.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Pestalardo et al [8] reported total excision using a tissue expander. Both authors demonstrated excellent outcomes for the treatment of AKN-associated alopecia, but both maneuvers required multistage surgery [1] [6] [8]. Although long scars might re-…”
Section: Discussionmentioning
confidence: 99%
“…Acne keloidalis nuchae (AKN) is an idiopathic chronic inflammatory condition characterized by the formation of papules and pustules that ultimately develop into keloid-like masses on the occiput and nape of the neck [1] [2]. This hyperproliferative disorder typically occurs in young adult males of African origin [2] [3], but it is relatively rare in the Asian population [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations